(untitled) (London Journal of Research In Management & Business, 2025)
This paper show that rational choice on recursive decision under measure preserving transformation can lead to asymptotic behavior in a stationary environment, and providing sufficient conditions for recursive decision systems to possess ergodic properties from its stationary mean.